Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Which is the only solution to the equation [tex]$\log_3(x^2 + 6x) = \log_3(2x + 12)$[/tex]?

A. [tex]$x = -6$[/tex]
B. [tex][tex]$x = -2$[/tex][/tex]
C. [tex]$x = 0$[/tex]
D. [tex]$x = 2$[/tex]
E. [tex][tex]$x = 6$[/tex][/tex]


Sagot :

To solve the equation [tex]\(\log_3 (x^2 + 6x) = \log_3 (2x + 12)\)[/tex], let's follow a systematic approach.

### Step 1: Use properties of logarithms
Given that the logs are to the same base, we can set the arguments equal to each other:
[tex]\[ x^2 + 6x = 2x + 12 \][/tex]

### Step 2: Rearrange the equation
Move all terms to one side to form a quadratic equation:
[tex]\[ x^2 + 6x - 2x - 12 = 0 \][/tex]
[tex]\[ x^2 + 4x - 12 = 0 \][/tex]

### Step 3: Solve the quadratic equation
We solve the quadratic equation [tex]\(x^2 + 4x - 12 = 0\)[/tex] using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]

In this equation, [tex]\(a = 1\)[/tex], [tex]\(b = 4\)[/tex], and [tex]\(c = -12\)[/tex]. Substituting these values into the quadratic formula gives:
[tex]\[ x = \frac{-4 \pm \sqrt{4^2 - 4 \cdot 1 \cdot -12}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{-4 \pm \sqrt{16 + 48}}{2} \][/tex]
[tex]\[ x = \frac{-4 \pm \sqrt{64}}{2} \][/tex]
[tex]\[ x = \frac{-4 \pm 8}{2} \][/tex]

### Step 4: Calculate the potential solutions
This produces two potential solutions:
[tex]\[ x = \frac{-4 + 8}{2} = \frac{4}{2} = 2 \][/tex]
[tex]\[ x = \frac{-4 - 8}{2} = \frac{-12}{2} = -6 \][/tex]

### Step 5: Check domain restrictions
Since the original equation involves logarithms, we must ensure the arguments of the logarithms are positive. Therefore, both [tex]\(x^2 + 6x\)[/tex] and [tex]\(2x + 12\)[/tex] should be positive for the solutions to be valid.

- For [tex]\(x = 2\)[/tex]:
[tex]\[ x^2 + 6x = 2^2 + 6 \cdot 2 = 4 + 12 = 16 \][/tex]
[tex]\[ 2x + 12 = 2 \cdot 2 + 12 = 4 + 12 = 16 \][/tex]
Both expressions are positive.

- For [tex]\(x = -6\)[/tex]:
[tex]\[ x^2 + 6x = (-6)^2 + 6 \cdot (-6) = 36 - 36 = 0 \][/tex]
[tex]\[ 2x + 12 = 2 \cdot (-6) + 12 = -12 + 12 = 0 \][/tex]
Both expressions become zero, which is not within the logarithm's domain (logarithm of zero is undefined).

Hence, the valid solution is:
[tex]\[ \boxed{x = 2} \][/tex]